Kemampuan kerjasama, metode proyek,anak usia 4-5 tahun. - yektiningtyas, ira; Muzaqi, Sugito (MOTORIC, 2025)
ABSTRACT Cooperation skills are an important social aspect that needs to be developed in early childhood, especially children aged 4–5 years who are still in the egocentric stage. Cooperation helps children learn to share, interact positively, and understand the value of mutual cooperation. This study aims to improve the cooperation skills of group A children at Cempaka Putih Semampir Kindergarten, Surabaya through the application of the project method. The study used a Classroom Action Research design with the Kemmis and McTaggart model, implemented in two cycles, each consisting of three meetings. The research subjects were 18 children, consisting of 9 boys and 9 girls. The focus of the study included interaction skills, responsibility, and mutual assistance. Data were collected through observation and documentation, using observation sheets as the main instrument. Data analysis was carried out descriptively quantitatively. The success criterion was determined if the percentage of children's cooperation skills reached a minimum of 76%. The results showed a significant increase after the application of the project method. In the pre-action, children's cooperation skills were at 47%. After the first cycle, it increased to 63%, and in the second cycle it reached 83%, exceeding the predetermined indicator. This improvement is influenced by the syntax of the project method (2013), namely determining fundamental questions, preparing plans, implementing, and presenting projects. This activity structure provides space for children to interact, take responsibility, and help each other, so that cooperation skills develop optimally. Keywords: Collaboration ability, project method, children aged 4-5 years.